China-Pakistan Economic Corridor and Indian Print Media: The Case Study of Elite English Press - Dr. Muqarrab Akbar; Dr. Malik Adnan (Journal of Political Studies, 2018)
This study aimed to explore the treatment of Indian elite press towards the matter of China Pakistan Economic Corridor. The study deals with the quantitative and qualitative approaches in order to measure and examine the stance of the Indian Print media towards the said issue. For the purpose of analysis four English newspapers, The Times of India, The Hindu, Hindustan Times and Tribune India were selected during the June, 2016-December, 2017 as during this period CPEC was the hot debate in the regional media especially in India. All the news stories were coded against 5 categories with regard to Pak-China, Pak-India and China-India relations in the context of CPEC. The findings revealed that Indian Print media gave very negative coverage to the issue of CPEC in their news stories. The issue was framed as a bigger threat in the region, a militant support towards Kashmir conflict between both countries. Furthermore, it was also divulged that the proportion of negative coverage was greater than its positive coverage. Pakistan and China relations were framed as a deal to counter India for being closeness of CPEC route to Kashmir valley. Last but not the least, this project was considered a violation of Indian sovereignty with regard to its territory. The strategic interests were framed against the India which could lead to impact the peace in the Southeast Asia if the project is successfully executed.